Beyond Passive Immunity: Three Neonatal Influenza Cases Highlighting Impact of Missed Maternal Vaccination - Irina Profir; Cristina-Mihaela Popescu; Gabriel Valeriu Popa; Aurel Nechita (Clinics and Practice, 2025)
Background: Neonatal influenza is a rare condition. Young infants have immature immune defenses and are unable to receive direct vaccination; this can result in significant illness. Maternal anti-influenza immunization during pregnancy provides passive antibodies to the newborn via transplacental transfer, significantly decreasing the incidence and severity of influenza in early infancy. Nevertheless, the vaccination coverage during pregnancy remains low in many regions, leaving certain neonates without adequate protection. Methods: We present three cases of laboratory-confirmed influenza infection in neonates admitted to the “Sf. Ioan” Clinical Emergency Pediatric Hospital in Galați and conduct a literature review. The clinical presentation, co-infections, timing of antiviral therapy, laboratory findings, maternal vaccination status, and outcomes (including the hospitalization duration and recovery) were systematically analyzed for each case. Results: All three neonates were full-term and previously healthy, born to mothers who had not received influenza vaccinations during their pregnancies. They presented at ages ranging from 2 to 4 weeks with fever, respiratory symptoms including a cough, nasal congestion, and respiratory distress, as well as feeding difficulties. One case involved a co-infection with Bordetella pertussis, which manifested as a severe paroxysmal cough, cyanosis, and apnea. Laboratory findings in the cases with influenza alone indicated leukopenia accompanied by normal C-reactive protein levels. In the co-infection case, leukocytosis, lymphocytosis, and thrombocytosis were observed. All the infants received oseltamivir treatment within 48 h of the symptom onset; the case with pertussis co-infection also received azithromycin. Each infant required supplemental oxygen, but none necessitated mechanical ventilation. Clinical improvement was observed in all cases, with hospitalization ranging from 6 to 7 days and complete recovery without complications. Conclusions: Neonatal influenza may result in considerable morbidity, particularly in infants born to unvaccinated mothers. Positive outcomes, however, have been correlated with early diagnosis and antiviral treatment. Pertussis co-infection may exacerbate clinical progression, underscoring the importance of maternal immunization against both influenza and pertussis. In this case series, we aim to present three cases of laboratory-confirmed influenza in neonates born to mothers who were not immunized against influenza during pregnancy. These cases highlight the clinical presentations of neonatal influenza, underscore the risks associated with pertussis co-infection, and reinforce the importance of maternal influenza and Tdap vaccination for preventing severe outcomes in newborns.